On the Synthesis of Equivalent Circuit Models for Multiports Characterized by Frequency-Dependent Parameters - Neumayer, Roland; Stelzer, Andreas; Haslinger, Friedrich; Weigel, Robert (IEEE Transactions on Microwave Theory and Techniques, 2002)
The synthesis of lumped-element equivalent circuits for time-domain analysis of problems with frequency-dependent parameters is of great interest in microwave theory. This paper presents a systematic approach to generate minimal-order realizations for passive microwave circuits characterized by either admittance, impedance, or scattering-parameter data. In addition, a very efficient method to ensure inherent system properties such as stability and passivity is described. The proposed method is suitable for simulating frequency-response-based linear subnetworks in a general circuit environment consisting of lumped/distributed elements and nonlinear devices. Modeling examples for a two-, four-, and ten-port system with nonlinear and linear terminations, respectively, are given.
elib2cris::1512001600,neumayer2002b
Keywords: Model; Synthesis